Louis Lochner papers - Lochner, Louis Paul, 1887-1975.; Lochner, Louis Paul, 1887-1975. (1914)
Papers relating directly to Fritz Kreisler, including letters, legal documents, honors, writings, programs, press releases, and clippings; papers pertaining to Lochner's biography of Kreisler, including notes and corrections, relevant correspondence, and other miscellaneous source material.
Journalist, biographer of Fritz Kreisler.
Forms part of: Kreisler, Fritz, 1875-1962. Fritz Kreisler collection, 1845-1966 (bulk 1910-1955).
Finding aid available in the Library of Congress Performing Arts Reading Room and on the Internet.
Louis Lochner papers of the Fritz Kreisler collection, Music Division, Library of Congress.
Keywords: Kreisler, Fritz, -- 1875-1962.; Lochner, Louis Paul, -- 1887-1975 -- Autographs; Lochner, Louis Paul, -- 1887-1975 -- Correspondence; Journalists -- United States -- Autographs; Journalists -- United States -- Correspondence